Der Irakkrieg 2003 - Eder, Franz (innsbruck university press, 2015)
Why did the Bush administration decide to go to war against Iraq in March 2003? The aim of this book is to give answers to this question. An integrative model for foreign policy analysis shows that the causes of this decision are both at the level of the individual (the heightened sense of threat triggered by 9/11), the level of the collective (the group consensus for a policy of "coercive diplomacy"). , as well as at the level of the international system (the image of the enemy Iraq). In summary, it is argued that in a political environment where the population demands maximum security, policy inevitably tends to overreact and wrong decisions become more likely.